Audible minorities and discrimination: an overview - Warkentin, Erwin (Ñemitỹrã, 2020)
This article deals with research into the importance of native or near native pronunciation of a person’s L2 or L3 and the prejudices faced by those who may speak an accented form of a majority language. In order to reach its conclusions, the article analyses research focused on the learning of English as an L2 or L3 undertaken over the last 50 years. It concentrated on the impact of accented speech and the biases for and against accented speakers of a majority language and identifies where these findings converge and diverge. These results also indicate that the concerns of researchers have shifted as the perceptions of foreigners within English-speaking societies have changed over time. Ingroups are identified as important in determining the relative values of accents and that accented speakers constitute an audible minority and exert pressure on its members to maintain the “accentedness” of their speech. In defining the nature of an audible minority, the article indicates that this can be as powerful a factor as that of skin colour in some societies. In the end, it questions whether meticulous uniformity in spoken language is important or even desirable. The article concludes by suggesting that the problem of the audible minority is more that of the listener than the speaker since many of the myths surrounding accentedness and intelligibility have been proven false.